ANALYSIS OF THE RELATIONSHIP BETWEEN THE PRODUCER PRICE INDEX AND THE CONSUMER PRICE INDEX IN INDONESIA’S AGRICULTURAL SECTOR - Brenda Putri Br Sinuhaji; Syarif Imam Hidayat; Dita Atasa (Jurnal Mahasiswa Agribisnis, 2026)
Price index is an important tool for measuring price changes at both the producer and consumer levels through the Producer Price Index (PPI) and the Consumer Price Index (CPI). The relationship between these two indices remains a controversial issue, particularly in Indonesia’s agricultural sector, which is characterized by complex market structures, including small-scale enterprises, dependence on natural factors, and lengthy distribution chains. This study aims to analyze the short-term and long-term relationships between the PPI and CPI in Indonesia’s agricultural sector over the period 2013–2023. Secondary data were obtained from Bank Indonesia and the Central Statistics Agency (Badan Pusat Statistik) and analyzed using the Augmented Dickey-Fuller (ADF) stationarity test, Johansen cointegration test, and Vector Autoregression (VAR) estimation. The results indicate that there is no cointegration between the PPI and CPI, implying the absence of a long-term relationship. The VAR(1) estimation further shows that the PPI and CPI do not influence each other in the short run, except for the PPI’s influence on itself. These findings highlight the presence of asymmetric price transmission, where changes in producer prices are not always passed on to consumers. Keywords: Producer Price Index, Consumer Price Index, Johansen Cointegration, Vector Autoregression, Agricultural Sector, Indonesia